When You Know Better You Do Better: Creating Cultural Safety for Black Patients - Riley-States, Olivia; Crossman, Renee (Atlantis, 2026)
Background: Western healthcare is inundated with processes that don’t meet the cultural needs of racialized populations or consider non-medical aspects of health and healing. Social structures and power imbalances make it difficult to change these processes. The health experiences of Black people are affected by mistrust, racial microaggressions, and discrimination. To foster health and healing, we must consider the harm done when care is not culturally responsive. Methods: To address the lack of culturally safe healthcare, we completed a quality improvement project to develop an educational workshop about cultural safety with Black patients. The workshop was created using the theoretical lens of relational inquiry and included a literature review, environmental scan, and consultations. The workshop is designed to challenge providers to be self-reflective of their biases while developing an understanding of the health needs of Black patients, especially the African Nova Scotian (ANS) population. Results: The session has been delivered and evaluation feedback indicated positive experiences with some change in knowledge. Participants engaged in difficult discussions about bias and discrimination in their workplaces and themselves. Conclusion: Cultural safety education can positively impact healthcare providers' attitudes. Healthcare is multifaceted for Black people; healthcare providers must understand the intersection of anti-Black racism and health. Rebuilding trust with the Black community, acknowledging harm, and increasing representation in healthcare are necessary to address health disparities for Black people. Healing the relationship between ANS communities and the healthcare system requires critical reflection and targeted actions. Cultural safety education can initiate change.